2010
DOI: 10.1128/jcm.01164-10
|View full text |Cite
|
Sign up to set email alerts
|

Human Astrovirus Infection in a Patient with New-Onset Celiac Disease

Abstract: Many diseases with unknown etiology may be caused by unidentified viruses. Sequence-independent amplification revealed a new astrovirus, similar to VA1, in a 4-year-old male diagnosed with celiac disease. This expands the geographic range of this virus to include Europe and may associate astrovirus infection with the onset of celiac disease.Infectious diseases pose a continuous disease burden on humans, and many diseases with unknown etiology may be caused by unidentified viruses. Key to effectively counter th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The presence of these novel AstVs has been documented in several countries, including Australia, China, India, Nepal, the Netherlands, Nigeria, Pakistan, and the United States, but not in Japan (19,20,22,23,47,48). We identified MLB-AstVs in all influent samples collected between November 2007 and March 2008.…”
Section: Discussionmentioning
confidence: 84%
“…The presence of these novel AstVs has been documented in several countries, including Australia, China, India, Nepal, the Netherlands, Nigeria, Pakistan, and the United States, but not in Japan (19,20,22,23,47,48). We identified MLB-AstVs in all influent samples collected between November 2007 and March 2008.…”
Section: Discussionmentioning
confidence: 84%
“…Serological studies in the United States have confirmed that HAstV-HMO-C (VA1) is a highly prevalent human-infectious agent (115). In a recent study, a strain closely related to HAstV-VA1 was isolated in a patient with new-onset celiac disease (114). Finally, similarly to what has been observed for classic HAstVs, extraintestinal dissemination in immunodeficient individuals has also been observed in HAstV-HMO-C (VA1) virus infections, when the agent was detected in neural tissue from an immunocompromised child with encephalitis (116).…”
Section: Clinical Disease Correlatesmentioning
confidence: 99%
“…HAstV-VA/HMO (VA1, VA2, and VA3 [also known as HMO-C, HMO-A, and HMO-B, respectively] and VA4) have been detected in pediatric gastroenteritis samples in Nigeria, Nepal, and Pakistan (29), the United States (27), Egypt (107), and China (109), but so far they have never been reported in Europe (114). Serological studies in the United States have confirmed that HAstV-HMO-C (VA1) is a highly prevalent human-infectious agent (115).…”
Section: Clinical Disease Correlatesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as reported in other autoimmune diseases [2,7,9,29,31], there is emerging evidence in favor of the importance of nondietary environmental factors in the later CD and especially the role of environmental factors related to the season of birth. In particular, the infectious diseases caused by rotavirus and astrovirus [30,32,37] as well as the fluctuating vitamin D level might be reflected in a seasonal variation in CD risk related to month of birth [19,28,34].…”
Section: Introductionmentioning
confidence: 99%